DOES SELF-EFFICACY PLAY AN INTERVENING ROLE? STUDYING BETWEEN ORGANIZATIONAL CLIMATE AND JOB INVOLVEMENT - Yusnita, Nancy (UNIVERSITAS PAKUAN, 2021)
Many pieces of research on job involvement had generated findings that job involvement is considered to be one of the main ways to increase employees' performance. The objective of this study is to examine factors that have a relationship with job involvement namely organizational climate and self-efficacy. By finding the important factors that influence job involvement, it is expected that efforts to increase job involvement are useful for enhancing performance This study was conducted among lecturers at 4 private universities in Bogor, Indonesia. The sample for the study consisted of 252 lecturers derived randomly from its population. The study mainly utilized quantitative data (from questionnaires). The regression analysis was used to find out the relationship among variables. The findings revealed that organizational climate had a positive effect on job involvement. Similarly, self-efficacy had a positive effect on job involvement. The further organizational climate had a positive effect on job involvement through self-efficacy. The research result showed that self-efficacy as the intervening had significant a role in the effect of organizational climate on job involvement. Also, based on those findings, this study proposed some recommendations toward private universities to strengthening the self-efficacy of the lecturers to increasing their job involvement to increase performance